The Effect of Reward and Punishment on Work Discipline - Sandi Nasrudin Wibowo; Ade Solahudin; Bagus Eka Haryanto; Yuni Widawati (Research Trend in Technology and Management, 2023)
The purpose of this research is to 1] test and analyze the effect of partial rewards on the work discipline of employees of PT. Brass Mega Building; 2] partially test and analyze the effect of punishment on the work discipline of PT. Brass Mega Building; and 3] testing and analyzing the effect of reward and punishment simultaneously on the work discipline of PT. Brass Mega Building. The research method used is descriptive and verification methods. The population in this study were all employees of PT. Kuningan Mega Building, Kuningan Regency, totaling 52 employees with a sampling technique using a saturated sample (Sesnus) so that the entire population was used as the research sample. The data analysis method used is multiple linear regression analysis. The results of this study indicate that Reward (X1) has a positive and significant effect on Work Discipline (Y) employees of PT. Kuningan Mega Building, Punishment (X2) has a positive and significant effect on work discipline (Y) employees of PT. Kuningan Mega Building, and Reward (X1) and Punishment (X2) simultaneously or jointly have a positive and significant effect on work discipline (Y) employees of PT. Kuningan Mega Building Kuningan district. This study verifies previous studies that reward and punishment either partially or simultaneously have a positive and significant effect on work discipline. This means that the higher the reward and punishment applied to a company, the higher the level of work discipline in the company.